Exploring driving behaviour from the perspectives of individuals with chronic pain and health professionals. (July 2022) - Vaezipour, Atiyeh; Andrews, Nicole; Oviedo-Trespalacios, Oscar; Amershi, Fatima; Horswill, Mark; Johnston, Venerina; Delhomme, Patricia
Abstract: Chronic pain affects one in five Australians, and this could impact daily activities such as driving. Driving is a complex task, which requires the cognitive and physical ability to predict, identify, and respond to hazards to avoid crashing. However, research exploring the factors that influence safe driving behaviour for chronic pain individuals is limited. A qualitative study was conducted which involved semi-structured interviews with 23 people who had experienced persistent pain for at least three months and 17 health professionals who had experience working with individuals with chronic pain. The aim of this study was to obtain a deeper understanding of the experiences and challenges that people with chronic pain may have in their day-to-day driving. Participants were also asked about currently available driving assessments and strategies for individuals with chronic pain in the Australian healthcare system. The themes emerging from the interviews highlighted the need for clearer guidelines and educational materials regarding the impact of chronic pain on an individual's ability to drive. These themes included the physical and cognitive challenges resulting from chronic pain, as well as the potential side effects of pain medications. In addition, participants identified a number of self-regulation strategies and driving assessments currently available for monitoring safe driving behaviour in Australia. This study improves our understanding of how chronic pain affects driving behaviour, as reported by individuals experiencing the pain and relevant health professionals. Recommendations for improving the safety of drivers with chronic pain are discussed, including possible technological interventions and better public education. Highlights: Driving is a cognitively demanding task that may be compromised due to chronic pain. Chronic pain may negatively impact driving at the strategic, tactical and operational levels. Lack of clear guidelines makes it challenging to assess driving in short clinical timeframes.